Upaya Menurunkan Burnout Belajar Melalui Bimbingan Kelompok Teknik Role Playing Pada Siswa - Sofia Wulandari, Ewin Eka; Mutakin, Fakhruddin; Kinanthy Karamoy, Yurike (JKI (Jurnal Konseling Indonesia), 2024)
This study aims to determine the reduction of academic burnout through role-playing techniques among students at SMPN 02 Silo. This research is a counseling guidance action research. The subjects of the study were all seventh-grade students at SMPN 02 Silo, totaling 177 students, with 6 students selected through purposive sampling as the sample. Data collection was conducted using questionnaires. The results showed that 84% successfully exceeded the success indicators, with the sample experiencing a significant decrease in academic burnout. These findings indicate that group counseling services using role-playing techniques can effectively reduce academic burnout among students at SMPN 02 Silo. This study recommends that similar programs be implemented in other schools to test the generalizability of the findings and to explore other factors that may influence student academic burnout, such as social support and environmental influences. Thus, it can be concluded that group counseling with role-playing techniques can reduce students’ academic burnout.